Edukasi Bahaya Merokok Terhadap Sistem Pernapasan Bagi Anak di SDN 009 Batam - Rizki Sari Utami Muchtar Sari; Althafia Athaya; Azimah Nurilqolbi; Erlin Handriani (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2023)
Acute Respiratory Infection (ARI) is acute infection involving the upper respiratory tract and lower respiratory tract organ. Cigarette smoke can increase the frequency of ARI in children, where children exposed to cigarette smoke are at risk of ARI more often than children who are not exposed to cigarette smoke. This service aims to provide an understanding to elementary school children how the dangers of smoking can affect breathing. The method of implementation is by providing education related to the dangers if smoking and demonstrating the dangers of smoking to students of SDN 009 Batam City. This community service concludes that smoking behavior in children is a form of socialization of children through agents around children. Agents that influence children's smoking behavior are family, friends, society, and the environment. Suggestions in this service for health workers to provide counseling to children regarding the dangers of smoking and the consequences caused by smoking.